Assessing the Drivers behind the Structure and Diversity of Fish Assemblages Associated with Rocky Shores in the Galapagos Archipelago - Stijn Bruneel; Wout Van Echelpoel; Long Ho; Heleen Raat; Amber Schoeters; Niels De Troyer; Ratha Sor; José Ponton-Cevallos; Ruth Vandeputte; Christine Van der heyden; Nancy De Saeyer; Marie Anne Eurie Forio; et al. (Journal of Marine Science and Engineering, 2021)
Oceanic islands harbor unique yet fragile marine ecosystems that require evidence-based environmental management. Among these islands, the Galapagos archipelago is well known for its fish diversity, but the factors that structure communities within and between its islands remain poorly understood. In this study, water quality, physical habitats and geographical distance were assessed as potential predictors for the diversity and structure of fish assemblages. Differences in the structure of fish assemblages of the two studied islands (Santa Cruz and Floreana) were most likely driven by temperature and nutrient concentrations. In the relatively highly populated island Santa Cruz, the structure of fish assemblages was more affected by water conditions than physical habitats while the contrary was true for the more pristine area of Floreana. A wide variety of species with different geographical origins were distributed over the different islands, which indicates that most fish species are able to reach the islands of the archipelago. However, temperature gradients and elevated nutrient levels cause large differences in the structure of local fish assemblages. In addition, in Santa Cruz nutrient concentrations were negatively correlated with <semantics>α</semantics> diversity. Since pollution is a clear pressure on the fish assemblages of oceanic islands, environmental management of the coastal areas is of paramount importance.